REDESAIN TAMPILAN USER INTERFACE APLIKASI DOCUMENT MANAGEMENT SYSTEMS DENGAN METODE USER CENTERED DESIGN PADA PT PGAS SOLUTION - Nona Intan Maulani (2022)
Document Management System (DMS) is a web-based application that is used to manage and store documents in the company. DMS electronically loads documents and processes documents such as Work Reference Documents, Work Instructions starting from those documents still in draft form, reviewed, published, and stored. The purpose of this study is to analyze and assess the usability level of Document Management Systems and provide suggestions or recommendations for user interface design using the User Centered Design method. This study uses a User Centered Design Method approach with 19 CSUQ questionnaire questions as a usability measurement tool. The author hopes that the results of this research will be able to help and provide solutions to PT PGAS Solution in improving the quality of DMS applications, so that these applications can work more effectively and efficiently with a new look.